Study on Corrosion Behavior of Ultra-High Strength Marine Engineering Steel EH890 in Simulated Marine Environment - CHE Majun, MA Xinyuan, DU Xiaojie, LI Hengkun, XU Zhenlin (Cailiao Baohu, 2023)
In order to meet the development needs of steel for marine engineering，the high strength and high corrosion resistance marine engineering steel EH890 containing Cu was designed and developed.The corrosion behavior of EH890 and EH460 in 3.5%NaCl solution was compared and analyzed by potentiodynamic polarization curve，electrochemical impedance spectroscopy，X-ray photoelectric analysis (XPS)，scanning electron microscope (SEM) and X-ray diffraction (XRD)，and the corrosion morphology and composition of corrosion products were discussed.Results showed that compared with EH460 steel，the corrosion current density of EH890 steel was reduced by 20%in 3.5%NaCl solution，and the charge transfer resistance Rt  increased by 1.6 times，indicating that EH890 had better corrosion resistance.After soaking in 3.5%NaCl solution for 7 d，the EH890 sample exhibited uniform corrosion characteristics，while EH460 exhibits uneven corrosion，with localized cracking of the surface rust layer.Furthermore，CuFeO2and NiFe2O4formed in the rust layer of EH890 improved the compactness of the rust layer at the initial stage of corrosion，inhibited the corrosion process，and improved the corrosion resistance of EH890 in 3.5%NaCl solution.